PENGARUH KESEHATAN DAN KESELAMATAN KERJA TERHADAP KINERJA KARYAWAN: (Studi Pada UD. Aira Fiberglass Maluku Tengah) - Pocerattu V. Alfonso (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2021)
UD. Aira Fiberglass is a company engaged in the manufacture of fiberglass-based boats and boats, a company located in Kaloli Village, Central Maluku. In 2019 out of 100 ships only 50 were completed, in 2020 out of 100 ships only 85 were completed and in 2021 out of 100 ships only 80 were completed due to frequent work accidents due to the lack of awareness of workers about the importance of using PPE when working. This study aims to assess how much influence occupational health and safety has on employee performance at UD. Aira Fiberglass Central Maluku. This type of research data is processed from the results of distributing questionnaires to UD employees. Aira Fiberglass as many as 30 people. The data analysis technique used in this study is multiple linear regression, to explain the description of research related to the hypothesis by using the analysis: validity test, t test (partial). Based on the results of data analysis for the significant test, the t test shows that the occupational health (X1) and occupational safety (X2) variables partially have a positive and significant effect on employee performance at UD. Aira Fiberglass.From the results of this study, it can be seen that occupational health and safety have a positive and significant effect on employee performance with multiple linear regression test results having a significant value of 0.000 below the 0.05 significant level, the significant level test results show significant level results for all variables below 0.05